Analysing Bullying as a Human Rights Violation: A Phenomenological Study of Law Students’ Perspectives in Higher Education - Nazla Audilla; Tafri Itsbatul Hukmi; Mulyana Mulyana; Ummi Hani (Yayasan Abdurrauf Cendekia Nusantara, 2026)
Every individual is entitled to a sense of security within their academic pursuits; however, bullying continues to threaten safety in educational environments, including higher education institutions. Despite its prevalence, research on bullying at the university level remains relatively limited compared to other educational settings. This study aims to explore students’ perceptions of bullying from a human rights perspective. Employing a qualitative approach with Creswell’s phenomenological method, data were collected through in-depth, semi-structured interviews with five law students selected using purposive sampling. The findings reveal that bullying is perceived as a complex phenomenon involving not only physical and verbal abuse but also power imbalances between perpetrators and victims, with impacts on psychological, social, and academic aspects. Moreover, students view bullying as a violation of human rights, particularly the rights to security, protection, and human dignity. These findings highlight the need for higher education institutions to establish preventive and educational strategies to address bullying, as well as to encourage active student involvement in creating a safer academic environment. [Setiap individu berhak memperoleh rasa aman dalam menjalani aktivitas akademiknya. Namun, bullying masih menjadi ancaman terhadap keamanan di lingkungan pendidikan, termasuk di perguruan tinggi. Meskipun fenomena ini cukup prevalen, kajian mengenai bullying di tingkat perguruan tinggi masih relatif terbatas dibandingkan dengan jenjang pendidikan lainnya. Penelitian ini bertujuan untuk mengeksplorasi persepsi mahasiswa terhadap bullying dalam perspektif hak asasi manusia. Penelitian ini menggunakan pendekatan kualitatif dengan metode fenomenologi Creswell. Data dikumpulkan melalui wawancara mendalam dengan panduan semi-terstruktur terhadap lima mahasiswa hukum yang dipilih melalui teknik purposive sampling. Hasil penelitian menunjukkan bahwa bullying dipersepsikan sebagai fenomena kompleks yang tidak hanya melibatkan kekerasan fisik dan verbal, tetapi juga ketimpangan kekuasaan antara pelaku dan korban, dengan dampak pada aspek psikologis, sosial, dan akademik. Selain itu, mahasiswa memandang bullying sebagai bentuk pelanggaran hak asasi manusia, khususnya terhadap hak atas rasa aman, perlindungan, dan martabat manusia. Temuan ini menegaskan pentingnya perguruan tinggi untuk mengembangkan strategi preventif dan edukatif dalam menangani bullying, serta mendorong keterlibatan aktif mahasiswa dalam menciptakan lingkungan akademik yang aman.]